2020
DOI: 10.3390/foods9010083
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Methods to Determine the Degree of Substitution of Quinoa and Rice Starch Acetates, Propionates, and Butyrates: Direct Stoichiometry, FTIR, and 1H-NMR

Abstract: Rice and quinoa starch esters were prepared by acylation using short-chain fatty acid anhydrides with different chain lengths (acetic, propionic, and butyric anhydride). A direct stoichiometric method based on the acylation reaction was used to determine the degree of substitution (DS) and acyl content (AC). In addition, Fourier-transform infrared spectroscopy (FTIR) was used to validate the conformational changes of acylated starch and 1 H-NMR was used as a DS reference method. DS by stoichiometric calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 29 publications
1
15
0
1
Order By: Relevance
“…After the reaction between CFP and ODS, the absorption band at 2100 cm −1 , corresponding to Si–H groups, confirmed the successful conjugation of ODS with CFP [ 42 ]. For calculating the degree of substitution of OCFP, we normalized the intensity of the ν(Si–H) peak and weighed the CFP and OCFP [ 47 ]. The weight of CFP (0.346 g) increased to 0.464 g after the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…After the reaction between CFP and ODS, the absorption band at 2100 cm −1 , corresponding to Si–H groups, confirmed the successful conjugation of ODS with CFP [ 42 ]. For calculating the degree of substitution of OCFP, we normalized the intensity of the ν(Si–H) peak and weighed the CFP and OCFP [ 47 ]. The weight of CFP (0.346 g) increased to 0.464 g after the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in taste retention or mouthfeel between PS and QF could be explained by their structural differences. Quinoa starch has extremely small granules (0.3 to 2 µm) and A‐type polymorph crystallinity, whereas PS has large granules (30 to 100 µm) and B‐type polymorph crystallinity (Abdul Hadi, Wiege, Stabenau, Marefati, & Rayner, 2020; Kong, Lee, Kim, & Ziegler, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] In addition, it was concluded that for the achievement of high DS for the starch esterification by acetic, propionic or butyric acid it is necessary to follow reaction in water solution under controlled pH value. [ 14 ] On this manner, the values of DS obtained were in the range 0.0305–0.1361. For obtaining higher DS it is necessary to be used different catalysts such as alkaline, triethylamine or using pyridine as reaction medium.…”
Section: Introductionmentioning
confidence: 88%